Asymmetric synthesis, molecular modeling and biological evaluation of 5-methyl-3-aryloxazolidine-2,4-dione enantiomers as monoamine oxidase (MAO) inhibitors - ERDEM, SAFİYE (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2018)
Single enantiomers of the new 5-methyl-3-aryloxazolidine-2,4-diones have been obtained either by an asymmetric synthesis using the chiral pool strategy or by a semipreparative resolution of the racemic compound by HPLC on an optically active stationary phase. The single enantiomers were assayed for their in vitro monoamine oxidase (hMAO) inhibitory activity and selectivity. The most potent inhibitor among the studied compounds has been found as (5R)-3-phenyl-5-methyl-2,4-oxazolidinedione (compound 1-R) which appeared to be a good antidepressant drug candidate since it inhibited hMAO-A selectively, competitively and reversibly with K-i values in the micromolar range (0.16 +/- 0.01 mu M). To better understand the enzyme-inhibitor interaction and to explain the efficiency and selectivity of the compounds toward hMAOs, molecular modeling studies were carried out on new, high resolution hMAO-A and hMAO-B crystallographic structures. According to binding energies and inhibition constants obtained from molecular docking calculations, compound 1-R has been found as the most selective MAO-A inhibitor and its weak binding affinities to MAO-B (large K-i values) led to the enhancement in MAO-A selectivity. It bounded in close proximity to FAD in the active site of MAO-A and situated near the aromatic cage by means of pi-alkyl interactions with Tyr407 and Phe352 whereas its position in MAO-B was 10 angstrom far from FAD and it was situated outside the Ile199 gate of the active site. None of the studied compounds showed any cytototoxicity on HepG2 cells at 1 and 5 mu M concentrations. (C) 2018 Elsevier Inc. All rights reserved.
Keywords: Asymmetric synthesis of 2,4-oxazolidinediones; Monoamine oxidase inhibitory activity; Molecular docking; Resolution via chiral HPLC; Toloxatone; 1-N-SUBSTITUTED THIOCARBAMOYL-3-PHENYL-5-THIENYL-2-PYRAZOLINES; REVERSIBLE INHIBITION; AROMATIC CAGE; B INHIBITORS; DERIVATIVES; BINDING; OXAZOLIDINONES; OPTIMIZATION; BENZYLAMINE; MECHANISM